IDEO method cards - IDEO (Firm) ([S.l.] : IDEO, 2003)
IDEO Method Cards show 51 of the methods we use to inspire great design and keep people at the center of our design process. Each card describes one method and includes a brief story about how and when to use it. The cards are divided into four categories Learn, Look, Ask, and Try making it easy to reference, browse, sort, and share the cards
Keywords: IDEO (Firm); Industrial design -- United States -- History -- 20th century; Design -- United States -- History -- 20th century; Design services -- United States; Creative ability in business; Technological innovations; New products -- Design